Late Quaternary Paleoceanography and Sedimentary Environments in Hudson Strait - Vilks, G.; MacLean, B.; Deonarine, B.; Currie, C.; Moran, K. (Géographie physique et Quaternaire, 1989)
ABSTRACTAirgun and high resolution Huntec seismic reflection profiles are interpreted to show up to 130 m of glacial, glaciomarine and postglacial sediments overlying bedrock. In a basin at the eastern entrance to Hudson Strait most of the surficial sediment was deposited during the last déglaciation, but in western Hudson Strait multiple till sequences from previous glaciations are recognized. Five acoustic units were identified, at least three of which were penetrated with piston cores. Foraminifera of the stratigraphically deepest core in the eastern basin indicate a proximal glaciomarine environment and a likely presence of an ice shelf. A 14C date of 8060 ± 70 yBP (TO 750) on molluscan shells gives a minimum age for the top of the acoustically laminated distal glaciomarine sediments. The early postglacial foraminifera suggest a period of increased influence of offshore bottom waters restricted to the deep eastern basin. The surface sediments of all cores contain species indigenous of colder and fresher inshore waters of the present time. The ratio of 18CV16O in the benthic foraminifer Cibicides lobatulus is herein related to bottom salinity. Downcore measurements of 8'8O on C. lobatulus tests indicate bottom paleosalinities lower by about 0.5%o shortly before the dated horizon of 8000 yBP. By this time Hudson Strait was sufficiently clear of glacial ice for establishment of the present tidal regime. The lower bottom salinities indicate that tidal mixing took place between glacial meltwater leaving Hudson Bay and the offshore counterflow. This process is thought to have reduced the sharpness of the salinity difference between the offshore water and the surface plume of Laurentide meltwater as it entered the ocean.